Identification from measurements of mechanical fields by finite element model updating strategies - Ienny, Patrick; Caro-Bretelle, Anne-Sophie; Pagnacco, Emmanuel (European Journal of Computational Mechanics, 2009)
Inverse problem resolution methods are widely used in the determination of material behaviour. The optimisation of the parameters, as inputs into a well-defined system, is obtained from observed outputs such as kinematic field measurements. The aim of this paper is to summarize the research concerning one inverse method, Finite Element Modelling Updating, based on the use of these field measurements. This method is based on a combination of three components, described in the following three sections. First we present the optical field measurements applied to multi-axially loaded objects, together with their performances. Then we outline the use of Finite Element Modelling for achieving a correlation between numerical fields and their experimental counterparts. Finally we describe the identification process, together with cost functions, minimisation procedure and model validation analysis.